2013
DOI: 10.5901/ajis.2013.v2n2p365
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s Productivity in Promoting Quality Education in Public Primary Schools in Kenya

Abstract: Researchers and policy makers agree that teacher quality is a pivotal issue in education. Quality education begins with quality teachers. Excellent teachers do more than teach the curriculum content: they inspire and enthuses their pupils and serve as role models in terms of attitudes and social relationships. This paper discusses factors that may affect the productivity of teachers in promoting the quality of education in Kenya.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The test result shows that the r calculated value of 0.887 was less than the r critical value of 0.897, with a probability value of 0.010 and a degree of freedom of 352. The statistics reveals that the null hypothesis is retained while the alternate hypothesis is The work of Kagwiria (2016) support the finding of the study as it revealed that power is concentrated in the hands of the leader who makes all the decisions, provides direction and assigns the task to subordinates. Men and Stacks (2013) arguing in the same vein stated that autocratic leaders are charismatic and self-assured individuals who typically do not require validation from their followers.…”
Section: Hypothesis Onesupporting
confidence: 62%
“…The test result shows that the r calculated value of 0.887 was less than the r critical value of 0.897, with a probability value of 0.010 and a degree of freedom of 352. The statistics reveals that the null hypothesis is retained while the alternate hypothesis is The work of Kagwiria (2016) support the finding of the study as it revealed that power is concentrated in the hands of the leader who makes all the decisions, provides direction and assigns the task to subordinates. Men and Stacks (2013) arguing in the same vein stated that autocratic leaders are charismatic and self-assured individuals who typically do not require validation from their followers.…”
Section: Hypothesis Onesupporting
confidence: 62%
“…There is a need to resource the curriculum with good quality faculty (Jitka, 2009) because e cient delivery depends on having a su cient supply of appropriately trained and motivated teachers. …, they inspire and enthuse … and serve as role models in terms of attitudes and social relationships" (Kagwiria, 2013). Teaching practice enables student-teachers to acquire beginning teaching competencies (Jitka, 2009;Mutende, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To ensure educational success, it is crucial that teachers are well-educated, intelligent, and dedicated to their profession. The quality of teachers is considered the root of quality education (Kagwiria & Amukowa, 2013), making the recruitment of qualified educators a fundamental necessity for educational advancement. Despite the importance of teaching, Kyriacou and Coulthard (2000) argued that the profession struggles to attract bright young minds.…”
Section: Introductionmentioning
confidence: 99%